Warming Effects of Spring Rainfall Increase Methane Emissions From Thawing Permafrost - Neumann, Rebecca B.; Moorberg, Colby J.; Lundquist, Jessica D.; Turner, Jesse C.; Waldrop, Mark P.; McFarland, Jack W.; Euskirchen, Eugenie S.; Edgar, Colin W.; Turetsky, Merritt R. (Geophysical research letters, 2019)
Methane emissions regulate the near‐term global warming potential of permafrost thaw, particularly where loss of ice‐rich permafrost converts forest and tundra into wetlands. Northern latitudes are expected to get warmer and wetter, and while there is consensus that warming will increase thaw and methane emissions, effects of increased precipitation are uncertain. At a thawing wetland complex in Interior Alaska, we found that interactions between rain and deep soil temperatures controlled methane emissions. In rainy years, recharge from the watershed rapidly altered wetland soil temperatures, warming the top ~80 cm of soil in spring and summer and cooling it in autumn. When soils were warmed by spring rainfall, methane emissions increased by ~30%. The warm, deep soils early in the growing season likely supported both microbial and plant processes that enhanced emissions. Our study identifies an important and unconsidered role of rain in governing the radiative forcing of thawing permafrost landscapes. Plain Language Summary Because the world is getting warmer, permanently frozen ground around the arctic, known as permafrost, is thawing. When permafrost thaws, the ground collapses and sinks. Often a wetland forms within the collapsed area. Conversion of permanently frozen landscapes to wetlands changes the exchange of greenhouse gases between the land and atmosphere, which impacts global temperatures. Wetlands release methane into the atmosphere. Methane is a potent greenhouse gas. The ability of methane to warm the Earth is 32 times stronger than that of carbon dioxide over a period of 100 years. In our study, we found that methane release from a thaw wetland in Interior Alaska was greater in rainy years when rain fell in spring. When spring rainwater entered the wetland, it rapidly warmed wetland soils. Rain has roughly the same temperature as the air, and during springtime in northern regions, the air is warmer than the ground. The microbial and plant processes that generate methane increase with temperature. Therefore, wetland soils, warmed by spring rainfall, supported more methane production and release. Northern regions are expected to receive more rainfall in the future. By warming soils and increasing methane release, this rainfall could increase near‐term global warming associated with permafrost thaw. Key Points In rainy years, recharge from the watershed rapidly altered wetland soil temperatures, affecting sedge abundance and methane emissions When wetland soils were warmed by spring rainfall, growing‐season methane emissions increased by ~30% By advecting thermal energy into soil, precipitation regulates the near‐term global warming potential of thawing permafrost landscapes